An update on urethral diverticula: Results from a large case series - Pirpiris, Athina; Chan, Garson; Chaulk, Richard C.; Tran, Henley; Liu, Madalena (Canadian Urological Association Journal, 2022)
Introduction: We aimed to describe the presentation, investigations, and management of patients with urethral diverticula and to review the importance of magnetic resonance imaging (MRI) in the diagnosis and surgical management of urethral diverticula. Methods: This was a retrospective review of female patients who underwent urethral diverticulectomies. This study was approved by the research ethics review board. Data was collected on patient demographics, presenting symptoms, investigations performed, operative technique, and minimum of two-year followup. Results: A total of 17 patients were included in this study, with a median age of 43 years. Most patients (70%) presented with a palpable vaginal lump; 64% presented with either lower urinary tract symptoms (LUTS) or recurrent urinary tract infections (UTIs). Patients underwent a preoperative MRI, which demonstrated that 59% of diverticula were distal and 53% were locally round. These imaging findings were consistent with the operative findings. MRI also demonstrated communication between the urethral diverticulum and the urethral lumen in 80% of cases, compared to only 47% endoscopically. Conclusions: The most common presentation of a woman with a urethral diverticulum is with either a palpable vaginal lump, LUTS, or recurrent UTIs. A high index of suspicion is required. Pelvic MRI appears to be an ideal imaging modality for the diagnosis of urethral diverticulum. A preoperative MRI is important to exclude alternative pathologies, appropriately counsel the patient, and assist with the surgical planning.